Newborn Screening and Genetic Analysis Identify Six Novel Genetic Variants for Primary Carnitine Deficiency in Ningbo Area, China - Yang, Xiangchun; Li, Qiong; Wang, Fei; Yan, Lulu; Zhuang, Danyan; Qiu, Haiyan; Li, Haibo; Chen, Liang (Frontiers in Genetics, 2021)
Primary carnitine deficiency (PCD) is an autosomal recessive disorder that could result in sudden death. It is caused by a defect in the carnitine transporter encoded by SLC22A5(Solute Carrier Family 22 Member 5, MIM:603377). Currently, a number of variants in SLC22A5 have been identified, however, the PCD prevalence and its variants in Ningbo area are unclear. In this study, we screened 265,524 newborns by using tandem mass spectrometry. Variants in SLC22A5 were further detected by next-generation sequencing in individuals with abnormal free carnitine levels (C0). We identified 53 newborns with abnormal C0 levels and 26 with variants in SLC22A5. Among them, 16 with two variants in SLC22A5 were diagnosed with PCD, suggesting the PCD birth prevalence in Ningbo city was 1/16,595. Moreover, the C0 level was significantly (P = 0.013) higher in PCD patients than in those with one variant. Besides, the c.1400C > G (p. S467C) and c.51C>G (p. F17L) variants were the most frequent and seven novel variants are all predicted to be damaging. This study reports the largest PCD patients in Ningbo area by newborn screening and expands the variant spectrum of SLC22A5. Our findings demonstrate the clinical value of combining NBS program results with DNA analysis for the diagnosis of PCD.